#TITLE_ALTERNATIVE# - AL FARUQ (NIM : 15410085), UMAR
Bus rapid transit is an affordable solution for mass public transportation in developing countries and also sustainable transportation systems. Although having Trans Metro Bandung (TMB) operating in Bandung, the city still suffer from heavy traffic jams, especially the corridors the TMB is operating in. TMB’s Corridor 2 serve the city’s commercial center but the majority of trip makers along the corridor still choose private-owned vehicles as their mode of choice instead of the already provided public transit. This study aims to find the factors affecting mode choice by trip makers who visit Corridor 2 regularly. The method used is the binomial logit model or logistic regression to see what factor or attribute has an effect on mode choice which then helps to calculate the probability of a given mode of transport. Analysis results can be used to predict which factors affect the selection of TMB. These results showed that the probability of TMB being chosen is 0.396714 while the probability for private vehicles is 0.603285. This indicates that TMB, as a mode, has a reasonable potential to take in riders from private vehicle users. From the sensitivity analyses it also found that trip expenses have a detrimental effect on mode choice, something to take note so that trip makers are more interested in taking the TMB to their destinations